Fiber-optic displacement sensor using a multimode bundle fiber - Yasin, Moh; Harun, Sulaiman Wadi; Karyono, Kusminarto; Ahmad, Harith (John Wiley & Sons, 2008)
A simple fiber optic displacement sensor based on intensity modulation technique is demonstrated using a bundle multimode plastic fiber as a probe. The sensor consists of a light source, a probe, and photodiode detector. The sensor is capable of measuring displacements of mirror ranging from 0.05 to 2.2 mm using a red light source of wavelength 632.8 nm with maximum output power of 1 mW. The sensitivity of the device is found to be 168.8 mV/mm over 0.05-0.35 mm range and -29.8 mV/mm over 1.05-2.2 mm range. The sensor is highly sensitive at the front slope and very useful for close distance target. The simplicity of the design, high degree of sensitivity, dynamic range and the low cost of the fabrication make it suitable for applications in industries as position control and micro displacement measurement in the hazardous region.